2021
DOI: 10.1016/j.annonc.2021.08.1155
|View full text |Cite
|
Sign up to set email alerts
|

642TiP Phase II CA184-585 (INSPIRE) trial of ipilimumab with nivolumab for molecular-selected patients with castration-resistant prostate cancer

Abstract: end points are safety and tolerability, PSA response rate, and ORR per RECIST v1.1 by blinded independent central review (BICR). Secondary end points are time to PSA progression, ORR, and rPFS per PCWG3-modified RECIST v1.1 by BICR; DOR and DCR per RECIST v1.1 and PCWG3-modified RECIST v1.1 by BICR; and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ongoing clinical trials are currently investigating the effect of ipilimumab and nivolumab for highly selected patients with mCRPC and a positive immune signature, aiming to achieve an increased clinical benefit (eg, NCT02601014 and NCT04717154). 29 30 Preliminary results from the NEPTUNES trial (NCT03061539) reported a favourable response rate in highly selected and pretreated patients, with a composite response rate of 26%.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing clinical trials are currently investigating the effect of ipilimumab and nivolumab for highly selected patients with mCRPC and a positive immune signature, aiming to achieve an increased clinical benefit (eg, NCT02601014 and NCT04717154). 29 30 Preliminary results from the NEPTUNES trial (NCT03061539) reported a favourable response rate in highly selected and pretreated patients, with a composite response rate of 26%.…”
Section: Discussionmentioning
confidence: 99%